Genome-Wide Comparative Analysis of Heat Shock Transcription Factors Provides Novel Insights for Evolutionary History and Expression Characterization in Cotton Diploid and Tetraploid Genomes - Liang, Yajun; Wang, Junduo; Zheng, Juyun; Gong, Zhaolong; Li, Zhiqiang; Ai, Xiantao; Li, Xueyuan; Chen, Quanjia (Frontiers in Genetics, 2021)
Heat shock transcription factors (HSFs) are involved in environmental stress response and plant development, such as heat stress and flowering development. According to the structural characteristics of the HSF gene family, HSF genes were classified into three major types (HSFA, HSFB, and HSFC) in plants. Using conserved domains of HSF genes, we identified 621 HSF genes among 13 cotton genomes, consisting of eight diploid and five tetraploid genomes. Phylogenetic analysis indicated that HSF genes among 13 cotton genomes were grouped into two different clusters: one cluster contained all HSF genes of HSFA and HSFC, and the other cluster contained all HSF genes of HSFB. Comparative analysis of HSF genes in Arabidopsis thaliana, Gossypium herbaceum (A1), Gossypium arboreum (A2), Gossypium raimondii (D5), and Gossypium hirsutum (AD1) genomes demonstrated that four HSF genes were inherited from a common ancestor, A0, of all existing cotton A genomes. Members of the HSF gene family in G. herbaceum (A1) genome indicated a significant loss compared with those in G. arboretum (A2) and G. hirsutum (AD1) A genomes. However, HSF genes in G. raimondii (D5) showed relative loss compared with those in G. hirsutum (AD1) D genome. Analysis of tandem duplication (TD) events of HSF genes revealed that protein-coding genes among different cotton genomes have experienced TD events, but only the two-gene tandem array was detected in Gossypium thurberi (D1) genome. The expression analysis of HSF genes in G. hirsutum (AD1) and Gossypium barbadense (AD2) genomes indicated that the expressed HSF genes were divided into two different groups, respectively, and the expressed HSF orthologous genes between the two genomes showed totally different expression patterns despite the implementation of the same abiotic stresses. This work will provide novel insights for the study of evolutionary history and expression characterization of HSF genes in different cotton genomes and a widespread application model for the study of HSF gene families in plants.